4z-7=5(5z-3)

Simple and best practice solution for 4z-7=5(5z-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z-7=5(5z-3) equation:


Simplifying
4z + -7 = 5(5z + -3)

Reorder the terms:
-7 + 4z = 5(5z + -3)

Reorder the terms:
-7 + 4z = 5(-3 + 5z)
-7 + 4z = (-3 * 5 + 5z * 5)
-7 + 4z = (-15 + 25z)

Solving
-7 + 4z = -15 + 25z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-25z' to each side of the equation.
-7 + 4z + -25z = -15 + 25z + -25z

Combine like terms: 4z + -25z = -21z
-7 + -21z = -15 + 25z + -25z

Combine like terms: 25z + -25z = 0
-7 + -21z = -15 + 0
-7 + -21z = -15

Add '7' to each side of the equation.
-7 + 7 + -21z = -15 + 7

Combine like terms: -7 + 7 = 0
0 + -21z = -15 + 7
-21z = -15 + 7

Combine like terms: -15 + 7 = -8
-21z = -8

Divide each side by '-21'.
z = 0.380952381

Simplifying
z = 0.380952381

See similar equations:

| (5b-1)(6b-3)= | | 2x+20=304 | | -6x-(9y+(5x-(-2y-b))-(2b+a))= | | 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 |

Equations solver categories